The Ichthyofauna of Lake Manguao, Taytay, Palawan, Philippines - Matillano, Joie D. (Annals of Tropical Research, 2002)
The fish fauna of Lake Manguao was investigated during two sample events last June and September 2002. The study was conducted in order to ascertain whether the unique fish fauna first catalogued by Day (1914) and later by Davies and Green (1990) is still present in the lake after the introduction of Oreochromis niloticus in 1992. This study also tried to find out whether there are two endemic species of Puntius in the lake, as described by Day (1914) and Herre (1924), or just one assumed by Davies and Green (1990), and if indeed a lake-endemic catfish is present in the area and to determine the local uses of the lake fishes Six types of fishing gears were used and a total of eight sampling stations were sampled representing both the littoral and open water zones of the lake. A total of 11 fish species from ten genera belonging to eight families including Anabantidac, Channidae, Cichlidae, Clariidae, Cyprinidae, Eleotridae, Hemiramphdae, and Siluridae were caught from the lake. In addition to the species previously accounted. for, a new fish species was recorded, Clarias macrocephalus, a native catfish of the Philippines. The two species of Puntuis collected by Day (1914) were also collected, as well as the silurid catfish described by Herre (1924) as Penisilurus palavanensis. Apparently, fishery focuses mainly on Tilapia and of secondary fishery importance are the other introduced species.